Cellulose-mediated floc formation by the activated sludge bacterium Shinella zoogloeoides ATCC 19623 - Na Gao; Jingcheng Dai; Yaqi Liu; Shuyang Li; Jing Wang; Wenxuan Lu; Dongru Qiu (BMC Microbiology, 2022)
Abstract Background Bacterial floc formation plays a central role in the activated sludge (AS) process. The formation of AS flocs has long been known to require exopolysaccharide biosynthesis. We had demonstrated that both expolysaccharides and PEP-CTERM (a short C-terminal domain includes a near-invariant motif Pro-Glu-Pro (PEP)) proteins were required for floc-forming in Zoogloea resiniphila MMB, a dominant AS bacterium. However, the PEP-CTERM proteins are not encoded in the genome of AS bacterium Shinella zoogloeoides ATCC 19623 (formerly known as Zoogloea ramigera I-16-M) and other sequenced AS bacteria strains. The mechanism underlying floc formation of Shinella and related AS bacteria remained largely unclear. Results In this study, we have sequenced and annotated the complete genome of S. zoogloeoides ATCC 19623 (aka I-16-M), previously isolated in USA and treated as the neotype for the AS floc-forming bacterium Zoogloea ramigera I-16-M, and another AS strain XJ20 isolated in China. Mariner transposon mutagenesis had been conducted to isolate floc-forming-deficient mutants in the strain ATCC 19623 as previously performed by using Tn5 transposon three decades ago. The transposon insertional sites of multiple mutants were mapped to the gene cluster for bacterial cellulose synthesis (bcs) and secretion, and the role played by these genes in floc-formation had been further confirmed by genetic complementation. Interestingly, the restriction map of this bcs locus-flanking region was highly similar to that of the previously identified DNA fragment required for floc-formation in 1980s. Cellulase treatment abolished the floc-forming phenotype of S. zoogloeoides ATCC 19623 but not that of Z. resiniphila MMB strain. The FTIR spectral analyses revealed that the samples extracted from S. zoogloeoides ATCC 19623 were cellulose polymer. Conclusion Our results indicated that we have largely reproduced and completed the unfinished pioneering work on AS floc-formation mechanism, demonstrating that the floc-formation and flocculating capability of Shinella were mediated by extracellular cellulose polymers.